The otter who wanted to know - Tomlinson, Jill 1931-1976 (London Egmont, 2014)
The story of an otter who learns to figure things out for herselfPat is an adorable little sea otter. She likes turning up her toes and floating in the sea, chasing fish, and asking a hundred and one questions. One day Pat's quiet life is turned upside down when she gets caught up in a pretty scary adventure. Suddenly she doesn't have time to ask any questions, and even if she did, no one would know the answers. This time Pat just has to find things out for herself.
b
b